If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + -14x + -72 = 0 Multiply x * x x2 + -14x + -72 = 0 Reorder the terms: -72 + -14x + x2 = 0 Solving -72 + -14x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -1x)(18 + -1x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(18 + -1x)' equal to zero and attempt to solve: Simplifying 18 + -1x = 0 Solving 18 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1x = 0 + -18 -1x = 0 + -18 Combine like terms: 0 + -18 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18Solution
x = {-4, 18}
| 6x+2=96 | | 7x+12=-2x-13 | | 0x*5x= | | 2u-6=-9u+9u+10 | | 7x=94 | | -(1+8m)=-1-8m | | 13-5-4-2+6= | | (m^2+2)[(m^2+3m-6)+(m^2-2m+4)]= | | 56x-34x=529 | | 12x-3x=-6x | | -96=-36+6x | | x+(59x)=180 | | 300?$0.90= | | -9a-17a+3a+4a+10a+3a= | | 7z+3z+6=90 | | x^4-32x+10=0 | | 4x^2+y^2-4xy=0 | | 82-x=41 | | 2+4x=-2(-2x-2) | | -15+6-5=x | | 75=5x*y | | 33x+56=55x+34 | | 5x-2y=20z | | 9w+184= | | x^24y^2-y+32=0 | | 8[4-(3-4x)]+3x=5(7x+4)-12 | | $0.90?300= | | 2(v-6)-4(v-1)=7 | | 2n+4=7 | | 6(x+4)-11=-15+10 | | 4x+2(x+y)= | | 6+7x=6x-10-3 |